Cashewnut and Cashew Apple – A Potential Drug and Medicine - Dewangan, Soumya; Ramteke, Vikas; Poyam, Sumitra (Chronicle of Bioresource Management, 2021)
Cashewnut is a versatile crop possess different medicinal properties. Nuts are used for several medicinal purposes and have great importance related to health as well as apples are used for fresh consumption, making pickles, preserves, chutneys and fermented and non-fermented beverages. Cashew apple juice has health benefits such as relief from chronic dysentery, sore throat, bone demineralization, rheumatism, neuralgia, boosts energy, facilitates the flexibility of blood vessels, good for weight loss due to presence of sugars, tannins, phenols, amino acids, ascorbic acid, minerals and fibre. Cashewnut shell liquid contains a mixture of products including anacardic acid, cardanol, cardol and 2-methylcardol. Cashew apple and nuts can be utilized commercially for processing however its potential is still demeaned in Indian economy.